ELECTRODYNAMIC FORCES IN PLAIN CONTACT ELEMENTS - A. N. Gerasimovich; D. A. Gerasimovich; Y. A. Klimovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper has proposed algorithms for calculation of shock electrodynamic forces acting on the layers of multi-layer plain contacts under short-circuit conditions based on electromagnetic force density, which is calculated with the account of non-uniform electromagnetic field distribution and with simplified current density distribution. Results pertaining to calculation of forces and their comparison are given in the paper. It has been shown that magnitudes of forces calculated in accordance with simplified algorithms exceed forces with due account of non-uniform field distribution by 5 ... 25 % .